Entre meios : do shopping ao lixo : análise dos processos de subjetivação na sociedade de consumo em sua interface com a produção de lixo - Viana, Flávia Passos (2007)
The transformations occurred on the contemporary societies one of the results of the dynamic of the globalized capitalist ways of production, are the interaction with the environment humans live. During this process, the production, of subjectivity is essential to the maintenance of the fragmented logic, individualist, and oriented to the necessity of profit. Therefore, the relationship established with time and space in constantly changing, being registered specially by the valorization of speed and spaces ever so shorter, denying the stagnation. The technology, by its turn, becomes an icon of this time, creating products and goods that easily become old and useless, as volatiles as the capital and the work that generates it. To make this possible, it counts with publicity and its capacity of making subjectivities into one only mass subjectivity. The final product of this dynamic shows itself on the exorbitant amount of garbage produced. This research is a study of the new ways of subjectivities created by the contemporary society of consume, through its relationship to the production of garbage. Discussing those aspects of reality is a relevant matter before the rare knowledge produced in this area and the necessity of articulation of this aspect of reality, commonly studied only in the technical researches. The study discusses those questions based on the concept of ecosophy proposed by Felix Guattari and brings the cartography as the approach of the research, on the theoretic construction, data collection and analyses. The place of research was limited to a residential building located in a noble neighborhood in Vitória/ES, where it was searched to know the ways of life of the people who were interviewed, the subjects discussed were: ways of life. consume and garbage. The analyses allowed noticing the resistance mechanisms, even when punctual, that live with the fragmentation and compartmentalization of the issues raised. The environment, here comprehended through the production of garbage, appeared as a transversal path on the discussion of the ways to live in the contemporary days, helping to bring up issues, worries and collective constructions to face the presented reality.